Text of lectures in the discipline "Financial diagnostics in anticrisis management" - Yurieva, Iryna; Tkachenko, M. O. (National Technical University "Kharkiv Polytechnic Institute", 2024)
The basic outline includes the main issues related to the theory and practice of diagnostics of financial condition in crisis management includes the theoretical foundations of diagnostics of financial condition in crisis management in different periods of its life, financial, technological, information component. The main attention is paid to the methods, financial diagnostics, functions, principles, methods of financial analysis of crisis management and their content. The essence and problems of diagonal analysis of the financial condition in crisis management, as well as the types and main stages in the diagnosis of crisis management are determined.
Keywords: text of lectures; economic mechanism; enterprise crisis; finance; rules of financing; crisis management